2021
DOI: 10.3389/fpsyg.2021.759701
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Academic Self-Efficacy in Relation to the Psychological Well-Being of University Students During COVID-19 in Venezuela

Abstract: Due to the COVID-19 pandemic, educational centers and universities in Venezuela have closed their physical plants and are migrating to emergency remote education to continue with academic programs. This empirical study aimed to analyze the predictive capacity of academic self-efficacy and emotional intelligence skills on each of the dimensions of psychological well-being. We employed a cross-sectional predictive design. The sample comprised 277 university students, of which 252 were female (91.00%). Their ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
1
15
0
4
Order By: Relevance
“…Meanwhile, Soncini et al (2021) argued that students’ academic self-efficacy in online learning courses can motivate them to have positive emotions such as pleasure and liking in online courses. In addition, García-Álvarez et al (2021) indicated that during the epidemic prevention and control period, students are prone to some negative emotions such as loneliness and anxiety in online courses if their academic self-efficacy is low. In summary, in the post-epidemic context, when students gain higher OAS-E, they are more likely to have positive emotions in online course learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Soncini et al (2021) argued that students’ academic self-efficacy in online learning courses can motivate them to have positive emotions such as pleasure and liking in online courses. In addition, García-Álvarez et al (2021) indicated that during the epidemic prevention and control period, students are prone to some negative emotions such as loneliness and anxiety in online courses if their academic self-efficacy is low. In summary, in the post-epidemic context, when students gain higher OAS-E, they are more likely to have positive emotions in online course learning.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, positive emotions can influence learners’ learning performance through individual factors such as enhanced self-efficacy and self-regulation ( Yu et al, 2022 ). Especially since the COVID-19 pandemic, some students have been prone to negative emotions such as anxiety, depression, isolation, and even the inability to consistently complete online learning tasks due to the impact of the epidemic prevention and control quarantine ( García-Álvarez et al, 2021 ). Moreover, studies have also found that pandemic-induced disruptions and uncertainty affect students’ academic self-efficacy to some extent, which may lead to negative emotions such as anxiety, worry, and fear ( Berman et al, 2022 ).…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…In addition, positive self-efficacy is a predictor of good academic performance (Yokoyama, 2019). Furthermore, self-efficacy has a strong correlation with mental health, which has been demonstrated in the results of different studies (e.g., Grøtan et al, 2019;García-Álvarez et al, 2021). For example, Tak et al (2017) shows that there is a negative relationship between academic self-efficacy and depressive symptoms in early to middle adolescence.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, to be happy, we must feel good about our everyday work. Above all, due to the restrictions of the pandemic and changed conditions in the home office, wellbeing is becoming increasingly important ( 45 ). When we are overly stressed, alarm bells go off in the body, and we feel unfocused and exhausted.…”
Section: Analysis Of Literature On the Role Of Sustainability In The ...mentioning
confidence: 99%